Strategi Branding Instagram dalam Membangun Citra Perusahaan: Studi Kasus pada @Pupukkujang - Khalisah, Najmi; Priatna, Wahyu Budi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This research analyzes the implementation of PT Pupuk Kujang's Instagram branding strategy. The study focuses on understanding the role of the digital branding strategy in shaping and strengthening the Corporate Image, which is assessed through the creation of positive Brand Awareness and Brand Association based on Aaker's Brand Equity theory. Employing a descriptive qualitative approach, data were obtained through semi-structured interviews with two key informants from September to November. The findings indicate that PT Pupuk Kujang implements a planned communication strategy through a monthly Creative Content Plan (CCP). The division of content pillars Kujang Pedia (for education), Kujang News (for credibility), and CSR content (for social responsibility) proved crucial. This content structure is effective in reinforcing the company's image as an educational, credible, and socially responsible entity in the eyes of the digital public. This strategy successfully enhances the company's brand equity. Pupuk Kujang is advised to maintain the consistency of CSR content for emotional closeness and to optimize Instagram's interactive features for more effective two-way communication.